MEDIA CASE-BASED LEARNING TO BUILD PEACE-LOVING CHARACTER IN STUDENTS PGSD STUDY PROGRAM - Arif Firmansyah; Nur Rahmah; Jeisi Riska Merdekawati Mentu (Universitas Tadulako, 2022)
This type of descriptive research is quantative with survey methods. The number of research samples as many as 103 students determined based on the calculation of samples according to Arikunto. Sampling techniques using purposive proportional random sampling consisting of students semester VI. Data collection is done by questionnaires, interviews, observations and documentation. Quantitative data analysis is presented in the categories